Effects of 6% tetrastarch or lactated Ringer's solution on blood coagulation in hemorrhaged dogs - Diniz, Miriely S. [UNESP]; Teixeira-Neto, Francisco J. [UNESP]; Goncalves, Daniele S. [UNESP]; Celeita-Rodriguez, Nathalia [UNESP]; Girotto, Carolina H. [UNESP]; Fonseca, Mariana W. [UNESP]; Takahira, Regina K. [UNESP] (Wiley-Blackwell, 2018)
Background Objective Tetrastarch solution (TS) can impair coagulation but the clinical relevance of this impairment is unclear in veterinary medicine. Compare the effects of volume replacement (VR) with lactated Ringer's solution (LRS) or 6% TS on coagulation in hemorrhaged dogs. Animals Methods Six healthy English Pointer dogs (19.7-35.3 kg). Prospective crossover study. Dogs were anesthetized without hemorrhage and VR (control). Two weeks later, dogs were hemorrhaged under anesthesia on 2 occasions (8-week washout intervals) and randomly received VR with LRS or TS at 3:1 or 1:1 of shed blood, respectively, aiming to decrease the hematocrit to 33%. Rotational thromboelastometry and other coagulation variables were determined before 0.5, 2, and 4 hours after VR during anesthesia and 24 hours after VR (conscious dogs). Results Conclusions and Clinical Relevance Buccal mucosal bleeding time did not differ between treatments after VR. Activated partial thromboplastin time increased from controls 4 hours after TS (P = 0.045). Clot formation time (CFT) and alfa-angle increased from controls from 0.5 to 4 hours after LRS (CFT, P <= 0.0001-0.02; alpha angle, P = 0.0001-0.02) and from 0.5 to 2 hours after TS (CFT, P = 0.0002-0.01; alpha angle, P = 0.0005-0.02). The maximum clot firmness decreased from controls from 0.5 to 4 hours after LRS (P <= 0.0001-0.01) and TS (P <= 0.0001-0.04). Tetrastarch does not impair primary hemostasis and induces transient dilutional coagulopathy that is similar to LRS because, when compared to a 3 times higher volume of LRS in hemorrhaged dogs, it does not cause greater interference on the viscoelastic properties of the coagulum.
Keywords: coagulation; colloids; crystalloids; hydroxyethyl starch; thromboelastometry